TISSUE RESPONSES AND HEALING PATTERN OF PERIOSTAL DEFECTS IN CALVARY BETWEEN TWO TYPES OF MEMBRANES PRODUCED THROUGH BIOENGINEERING: STUDY IN RABBITS - Ribas Filho, Josemael de Oliveira (2022)
Introduction: Simultaneously with the development of new biomaterials, numerous surgical modalities have been proposed, with the aim of promoting adequate regeneration of bone defects, without providing fenestrations or dehiscence. Among the regenerative techniques currently accepted for this purpose, guided tissue regeneration (GTR) stands out. Objective: To evaluate the healing pattern and the histological response of the organism to the insertion of a type A gelatin-based membrane, and to compare it with a commercial membrane. Methods: Fifteen adult rabbits were selected. In the parietal region of the calvaria, flaps were performed to create a supraperiosteal pouch and implantation of 2 types of resorbable membranes: Marquette membrane and Bio-Gide® membrane. After the surgical procedure, the animals were allocated into 3 randomly selected groups (n=5) for the period of euthanasia, which occurred at 2, 4 and 6 postoperative weeks. Subsequently, the calvaria areas were removed and stained by H&E and analyzed for periosteum formation, inflammatory infiltrate in the area of membrane insertion, membrane degradation/resorption, and perimembrane fibrosis. Results: A slight inflammatory infiltration occurred around the Bio-Gide® membrane and it underwent resorption during the postoperative period with periosteum reconstruction, predominantly of a fibrous nature. The Marquette membrane also did not trigger an important inflammatory reaction. However, there was no significant resorption during the period; there was also significant formation of fibrous capsule surrounding the entire membrane area. Conclusion: The Marquette membrane produces tissue isolation reaction, minimizing periosteal formation while not providing its degradation